Chronometr (1): Rozmowny budzik - Zieliński, Jan (Załącznik Kulturoznawczy, 2023)
The paper discusses several cases of using and abusing an authentic incident from the history of emigration from Galicia to the United States at the end of the XIX century, when a Jewish agent was cheating illiterate peasants who had never seen a clock before, pretending he was communicating with Hamburg and New York through a simple alarm-clock. The examples are drawn from the daily press of that time, various newspapers in the twenties and thirties, several books dealing with the subject of emigration as well as Martin Pollackʼs Kaiser von America (2010) and its stage adaptation in Bielsko-Biała (2013). Edward Bellamyʼs utopia Looking Backward is given as a counter-example, with its vision of an alarm-clock used as a source of pleasant music around the year 2000 – a vision realised in our world almost at the same time with a new generation of mobile phones.